THU0211 The Combination of Chinese Herbal Preparation Zheng Qing Feng Tong Ning with Methotrexate for The Treatment of Rheumatoid Arthritis: A Systematic Review and Meta-Analysis. (15th July 2016) - Feng, Z.; Cao, M.; Duan, L.; Wu, Z.
Abstract : Background: Traditional Chinese Medicine (TCM) and TCM preparations for the treatment of rheumatoid arthritis (RA) present its unique advantages, which show the characteristics of overall adjustment, multi-level and multiple targets, and with fewer side effects. Base on its potent immunosuppressive and anti-inflammatory properties, Sinomenine (SIN) or its preparations are taken into consideration for the treatment of RA. A kind of SIN preparations Zheng Qing Feng Tong Ning (ZQFTN) tablet combined with methotrexate (MTX) which was used to treat active RA. And there are several clinical researches showed that ZQFTN plus MTX significantly improved symptoms and prevented disease progression compared to MTX monotherapy. Owning to minor species and inconsistent assessment methods, the results always are paradoxical. Objectives: To assess the efficacy and safety of the combination of Chinese herbal preparation ZQFTN and MTX for the treatment of RA. Methods: Randomized controlled trials (RCTs) data of traditional Chinese preparation ZQFTN combined with MTX versus MTX alone for the treatment of RA were collected by searching the Pubmed, Embase, SpringerLink, CNKI and Wanfang databases up to December 2015. Study selection, data extraction, data synthesis, and data analyses were performed according to the Cochrane standards. Results: Ten RCTs involving 909 participants were included in this meta-analysis. Majority of the included RCTs had poor methodological quality. Compared with MTX, ZQFTN combined with MTX exhibited better therapeutic effects for the treatment of RA (OR=0.29; 95%CI: 0.17 to 0.50). In addition, ZQFTN combined with MTX caused more significant decrease in erythrocyte sedimentation rate (ESR) (MD=-7.40; 95%CI: -13.15 to -1.66), rheumatoid factor (RF) (MD=-14.02; 95%CI: -16.21 to -11.84), C reactive protein (CRP) (MD=-4.47; 95%CI: -7.17 to -1.78), and disease activity score in 28 joints (DAS28) (MD=-0.56; 95%CI: -0.74 to -0.37). Gastrointestinal discomfort and abnormal liver function were more frequently observed in RA patients treated with the combination of ZQFTN and MTX compared to MTX alone (OR=0.45; 95%CI: 0.22 to 1.01 for gastrointestinal discomfort; OR=0.24; 95%CI: 0.09 to 0.63 for abnormal liver function). No significant difference in low leucocyte account (OR=0.43; 95%CI: 0.17 to 1.11) was observed between the two groups. However, erythra with itching was more frequently reported in the MTX monotherapy group compared to the ZQFTN and MTX combination group (OR=4.43; 95%CI: 1.37 to 14.32). Additionally, publication bias was not identified based on the Begg's funnel plots and Egger's regression test. Conclusions: Our study suggests that ZQFTN combined with MTX are more effective than MTX alone for the treatment of RA. However, the adverse effects of the combination of ZQFTN and MTX should be further assessed. Due to the poor methodological quality of included trials, well designed, multi-center, and large-scale RCTs are necessary to further confirm our conclusion. Disclosure of Interest: Z. Feng Grant/research support from: Guangdong Provincial Natural Science Foundation (2015A030310067) and Shenzhen Technology Innovation Foundation (NO.JCYJ20150401171352927), M. Cao: None declared, L. Duan: None declared, Z. Wu: None declared